Використання модернізованого методу оптимізації цільових споживчих функцій під час обґрунтування застосування технологій нетрадиційної відновлюваної енергетики - Сусліков, Станіслав Вячеславович; Гаврись, Ольга Олександрівна; Усов, Максим Анатолійович (Чорноморський державний університет ім. Петра Могили, 2019)
Пропонується порівняльний аналіз математичних методів, підходів та інформаційних технологій (критеріїв на основі застосування ієрархічного методу залежностей, методу регресійного аналізу, методу біматричних ігор, теорії корисності, ELECTRE, аналізу часових рядів, регресійного аналізу та інших) по оптимізації інвестиційних планів для обґрунтування капітальних витрат при впровадженні технологій нетрадиційної відновлюваної енергетики. Запропоновано і апробовано модернізований метод оптимізації цільових споживчих функцій, за основу якого було взято метод ієрархій Т. Сааті по раціоналізації вибору технологій нетрадиційної відновлюваної енергетики. Даний метод був модернізованої, з точки зору використання конкретних цільових споживчих функцій (мінімізація за ціною; мінімізація за вагою; максимізація по середній температурі нагріву; максимізація по продуктивності гарячої води; максимізація по терміну служби; максимізація по гарантійним терміном служби) і їх раціоналізації в рамках проведеного комплексного дослідження з визначення найбільш сприйнятливих техніко-економічних показників геліоенергетічного обладнання, представленого на ринку України.

A comparative analysis of mathematical methods, approaches and information technologies (criteria based on the application of the hierarchical dependency method, regression analysis method, bimatrix games method, utility theory, ELECTRE, time series analysis, regression analysis and others) of optimizing investment plans for substantiating capital expenditures in the introduction of non conventional renewable energy technologies is proposed. The updated optimization of target consumer functions method, based on the T. Saati hierarchy method of choice rationalization of non conventional renewable energy technologies is proposed and tested. Modernization of the method allowed to form a well formalized approach to the collection of data by experts, taking into account the contradictions in judgments in the primary stages of the study; determine a set of criteria for optimization and their subsequent averaging, in order to determine the general target efficiency vector based on the application of specific target consumer functions (minimization by price; weight minimization; maximization by average heating temperature; hot water productivity maximization; service life maximization; warranty maximization); clustering the input data, which ultimately allows for a better perception of the research results. It has been highlighted that this method allows substantiate the choice of energy saving innovations (using solar energy technologies as an example) in the conditions of the particular economic entity more reliably. Approbation of the proposed method was carried out using the example of justifying and rationalizing the introduction of alternative renewable energy technologies as part of a comprehensive study of solar power equipment on the Ukrainian market (SintSolar CS, HC "SolarCompany", Logasol SKN 3.0 s, Atmosfera CBK — 30, Logasol SKS 4.0 s, Vaillant VFK 145 V, Vitosol 300 T). The conclusions on the application of the updated method considering the target consumer functions at high quality maximization of the parameters included in the system (technical and economic indicators and customer preferences) are drawn and the most appropriate option is highlighted.
Using the updated optimization of target consumer functions method for theoretical justification of application of alternative renewable power engineering technologies
Keywords: технології енергозберігаючі; нетрадиційна поновлювана енергетика; методи математичні; технології інформаційні; раціоналізація вибору; Сааті Т.; пріоритети цільові; energy-saving technologies; alternative renewable energy; mathematical methods; information technology; choice rationalization; Saati T.; target priorities